(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The threat of Corona Virus (Covid-19) has presented unique challenges for the institution of higher education, and it hit most aspects of life, including the education sector. This study aimed to investigate the effectiveness of online learning during the COVID-19pandemic. Data collection in this study was 113 respondent active students participated in this study at the Faculty of Islamic Education and Teacher Training, the State Islamic University of Banten. The sample collection method used simple random sampling conducted online. This research was a quantitative study using a survey method. The study analysed the effect of gender, age, and years of online learning experience differences on students’ perception of learning activities. This paper also explained about kinds of online learning used during the COVID-19 pandemic. It can be concluded that online learning was effective because the conditions that required online study and the lecturer-students talk as not as effective as in the normal classroom. The results of the study have implications for online lecturers, students, and administrators. Supports from institution and government are needed for the success of online learning.